Nepalese Landraces of Sponge Gourd for the Production of Tender Fruits - Bal, Kge; Tiwari, Radha K; KC, Hari B; Ghalo, Madhusudan; Gyawali, Sanjaya; Upadhyay, Madhusudan P (Journal of Agriculture and Environment, 2013)
Evaluation of landraces is necessary for better management of agricultural biodiversity on- farm. The objective was to evaluate the farmers named landraces of sponge gourd that are being maintained on-farm for tender fruit production. A total of 21 sponge gourd landraces collected from six districts of Nepal were evaluated in a randomized complete- block design with three replications at Agriculture Research Station, Malepatan, Pokhara, Nepal. These landraces were significantly (p = 0.05) different for first harvest days (p = 0.05) and fruit yield per plant (p = 0.05), highly significant (p < 0.01) for last harvest days, fruit-skin thickness, flesh thickness, fruit length, fruit perimeter, fruit weight and fruit number. Variation for tender fruits among these landraces can be utilized for improving the genotypes of sponge gourd as well as for long-term production in diverse environments.